PENGARUH MIND MAPPING TERHADAP PENINGKATAN EFIKASI DIRI MATEMATIKA DAN PRESTASI BELAJAR MATEMATIKA SISWA SMP - , Drs. Sudjiono, BA., S.Pd., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The excellence of mathematic learning achievements is vital importance to strive for the successful opportunity in future, thus it must be pursued. Meanwhile mind mapping as one of a learning strategy of mathematics that prioritize three brain management principles is very useful in helping students to organize, integrate information, and reconstruct their own knowledge. The purpose of this research is wanting to test the influence of mind map in increasing mathematics self-efficacy and learning mathematics achievements of students, and to see the influence of mathematics self-efficacy towards learning achievements of mathematics. As much as 107 students from Bendo Middle School 1 class VII is involved in this experiment, they are divided into two groups, which are 51 students as the experiment group and 56 students as control experiment. The scale of self-efficacy mathematics and mathematical learning achievement test are used as instruments to collect data. This research is using experiment method with scheme model of control group pre-test and post-test switching replications design. The data is analyzed with using the technique ANOVA (Analysis of Variance) on the gain scores, ANCOVA (Analysis of Covariance), and Simple Regression. The result of test ANOVA gain score is found that the strategy of mind mapping is influence significantly towards the increase of self-efficacy of mathematics with an effective contributions as much as (Î®2) 0,165, moderate category. The result of test ANCOVA is found that the strategy of mind mapping influence significantly towards the increasing mathematical learning achievements with an effective contributions as much as (Î®2) 0,131, moderate category. The result of test Simple Regression is found that self-efficacy of mathematics influence very significantly towards mathematic achievements, with predictive level as much as 37.3%.